Severe nose bleeding after intake of acetylsalicylic acid: von Willebrand disease type 2A - von der Weid, N. X.; Taleghani, B. Mansouri; Wuillemin, W. A. (Hämostaseologie, 2003)
This case report of a school boy with a history of severe and repeated episodes of epistaxis presents a short overview of the clinical and laboratory findings which lead to confirm the suspected diagnosis of von Willebrand disease (vWD). Suspicion of defective primary haemostasis should arise when unusual (because of their number or duration) mucosal bleeds appear in an otherwise normal and healthy patient. Because of its definitive inhibitory effect on platelet aggregation, acetylsalicylic acid (more than other non-steroidal anti-inflammatory drugs exerting unselective inhibition of cyclooxygenase) is a strong factor in triggering or sustaining the bleeding disorders in these patients. Among the congenital disorder of primary haemostasis, vWD is by far the most frequent one.The difficulties of laboratory diagnosis of vWD are stressed; the promises and pitfalls of new in vitro methods for measuring primary haemostasis (PFA-100® analyzer) are discussed. An accurate diagnosis of the specific type of vWD is of critical importance for correct patient management as well as for genetic counseling.
Keywords: Acetylsalicylic acid; epistaxis; von Willebrand disease